Jaurrieta 2005 Understanding Inflow Stream Discharge and Sediment Flux Variability, Linnédalen, Svalbard - ACADIS Community Support (Arctic Data Center, 2013)
Abstract: Climate change due to global warming in high latitude regions is causing ice caps and glaciers to melt. The melt, in turn, influences fluvial systems and may cause higher levels of stream discharge and sedimentation rates. In an attempt to map out significant climatic events of the modern Holocene period in the Svalbard Archipelago, Linnédalen (Linné Valley) was chosen as the field site to conduct arctic research. The goal is to study this area for the next three years and piece together a climate that can be directly lined to sediment deposition in Linnévatnet (Lake Linné). The purpose of this study is to understand what effect climate has had on the Kapp Linné landscape consisting of Linnébreen (Linne glacier), the glacier-fed braided stream, and the lake pouring out into the ocean during the modern Holocene. The focus of my research is the fluvial system at Linnéelva (Linné River). I examined the correlation between short term weather conditions, proglacial stream discharge, and sediment flux variability. I related stream discharge and stage by developing a rating curve. My results yielded an R2 value of 0.979, which is a high correlation. Stream discharge and sediment flux were influenced by temperature, which fluctuated with wind direction. Solar radiation varied inversely with temperature and did not correlate with stream discharge or sediment flux. These results will be used to interpret sedimentation rate variations in Linnévatnet (Lake Linné) and will help enhance future data collection techniques.